1995
DOI: 10.1128/jcm.33.12.3245-3251.1995
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Bartonella bacteremia in cats associated with cat-scratch disease patients

Abstract: Recent evidence supports a causal relationship between Bartonella (Rochalimaea) henselae, cat-scratch disease (CSD), and bacillary angiomatosis. Cats appear to be the primary reservoir. Blood from 19 cats owned by 14 patients diagnosed with CSD was cultured. Blood samples from cats owned by veterinary students (n ‫؍‬ 25) having no association with CSD or bacillary angiomatosis were cultured as controls. Eighty-nine percent (17 of 19) of cats associated with CSD patients and 28% (7 of 25) of controls were bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
5

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(87 citation statements)
references
References 37 publications
1
81
0
5
Order By: Relevance
“…The results of the present study suggest that neither FIV nor FeLV infection influences the prevalence of B. henselae infection in cats. Disease manifestation has not been reported in cats naturally infected with B. henselae, even in prolonged bacteremic cats (14,16). However, in some cases of feline lymphadenopathies of unknown cause, organisms microscopically resembling those associated with human CSD (19) were found in a silver-stained section of the mandibular, parotid and popliteal lymph nodes of cats (11,12).…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study suggest that neither FIV nor FeLV infection influences the prevalence of B. henselae infection in cats. Disease manifestation has not been reported in cats naturally infected with B. henselae, even in prolonged bacteremic cats (14,16). However, in some cases of feline lymphadenopathies of unknown cause, organisms microscopically resembling those associated with human CSD (19) were found in a silver-stained section of the mandibular, parotid and popliteal lymph nodes of cats (11,12).…”
Section: Discussionmentioning
confidence: 98%
“…antibody prevalence rates in cats. 5,19,[35][36][37] The majority of the studies reported to date have had small sample numbers or have varied widely in age distribution, which could have affected the results. Based on careful evaluation of prevalence data by age for the other reported studies, it appears that seroprevalence increases with age until cats reach 1-3 years of age, after which it plateaus or declines.…”
Section: Discussionmentioning
confidence: 99%
“…are recognized as primary pathogens in human diseases, including cat scratch disease, bacillary angiomatosis, endocarditis, and bacillary peliosis. [1][2][3] Bartonella infection has been associated with extended, often asymptomatic, intraerythrocytic bacteremia in domestic cats, [4][5][6][7][8] the primary mammalian reservoir host for Bartonella henselae. In addition, Bartonella spp.…”
mentioning
confidence: 99%
“…Prolonged periods of bacteremia have been documented in naturally infected cats for at least 15 months (Kordick et al 1995) and in experimentally infected cats for at least 454 days (Kordick et al 1999). In a study where female C57BL ⁄ 6 mice were infected with B. henselae, B. henselae-DNA could be detected for 94 days (Regnath et al 1998).…”
Section: Discussionmentioning
confidence: 99%